(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
inflation is one of the most important economic indicators that revolve around the process of formulating macroeconomic policies, because of its undesirable effects on the activities of economic units and the rates of economic growth. This study investigated the relationship between government spending and inflation in Iraq within the period (2005-2010), quarterly and monthly data, using modern econometrics methods in the analysis of time series represented in the form of Co-integration Model and Granger’s Causality. The results of the study revealed the existence of long-term equilibrium relationship between the variables mentioned, Causality test is also indicated the importance of government spending in the interpretation of the path of inflation during the period of study.